Wintertime Gas‐Particle Partitioning and Speciation of Inorganic Chlorine in the Lower Troposphere Over the Northeast United States and Coastal Ocean. Issue 22 (19th November 2018) - Haskins, Jessica D.; Jaeglé, Lyatt; Shah, Viral; Lee, Ben H.; Lopez‐Hilfiker, Felipe D.; Campuzano‐Jost, Pedro; Schroder, Jason C.; Day, Douglas A.; Guo, Hongyu; Sullivan, Amy P.; Weber, Rodney; Dibb, Jack; et al.
Abstract: The formation of photolabile chlorine reservoirs depend on how much chloride is available in the particle to react, which requires the chlorine partitioning to the particle in the troposphere to be well understood. However, limited measurements of gas and particle composition necessary to constrain this chemistry exist. We present measurements from the Wintertime Investigation of Transport, Emissions, and Reactivity (WINTER) aircraft campaign that show inorganic tropospheric chlorine compounds (Cl y ) measured in the lower troposphere are dominated by HCl and PM4 particulate chloride (pCl − ), with contributions from trace chlorine species like nitryl chloride (ClNO2 ), hypochlorous acid (HOCl), and molecular chlorine (Cl2 ). We observed elevated Cl y mixing ratios over the ocean (540–625 pptv) compared to over land (178–225 pptv). Observations show 0–20% (0–0.2 μg/m 3 ) of measured chlorine partitions into particles with a diameter less than 1 μm under typical WINTER conditions. The thermodynamic model, ISORROPIA II, overpredicts submicron pCl − by a factor of 2 but is brought into agreement, assuming a small fraction of unmeasured, refractory sea salt <0.1 μg/m 3 exists. The model‐measurement disagreement could also be caused by an effective equilibrium constant for HCl that is too large. We derive a lower‐limit equilibrium function ( K eq  = 2.5 × 10 6 exp[5, 208(1/ T  − 1/ T 0 )] mol 2 ·kg −2 ·atm −1 ) that lowers the model value's temperature dependency. This work provides constraints on Cl y in the troposphere, addresses the sensitivity of chlorine partitioning to minor changes in environmental variables, and highlights the remaining questions interfering with our ability to correctly model pCl − concentrations. Key Points: Airborne observations show that HCl and particle chloride are dominant tropospheric Cl y compounds in wintertime boundary layer Chlorine gas‐particle partitioning can be modeled, assuming a small, unmeasured fraction of NaCl mass from sea salt is internally mixed Lower‐limit equilibrium constant is derived for HCl from observations: K eq  = 2.5 × 10 6 exp[5, 208 (1/ T  − 1/ T 0 )] mol 2 ·kg −2 ·atm −1